2021
DOI: 10.1016/j.wneu.2020.11.004
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on Neurosurgical Services in Africa

Abstract: Introduction COVID-19 has affected the global provision of neurosurgical services. We sought to review the impact of COVID-19 on the neurosurgical services in Africa. Methods A cross-sectional survey was distributed to African neurosurgeons seeking to review demographics, national and neurosurgical preparedness, and change in clinical services in April 2020. Results A total of 316 responses from 42 countries were received. Of these, 81.6% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…A separate article covers the effect of COVID-19 on neurosurgery services and the psychosocial impact on African neurosurgeons. 5 The survey was discussed by the Continental Association of African Neurosurgical Societies (CAANS) Administrative Council.…”
Section: Methodsmentioning
confidence: 99%
“…A separate article covers the effect of COVID-19 on neurosurgery services and the psychosocial impact on African neurosurgeons. 5 The survey was discussed by the Continental Association of African Neurosurgical Societies (CAANS) Administrative Council.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, data on the pandemic’s effect on surgical outcomes from other LMICs are scarce, but the available evidence suggests that surgical services have substantially decreased during COVID-19. A 2021 survey of neurosurgeons in 42 African countries revealed that over half of respondents were not performing any elective operations during the pandemic, and they reported dramatic shortages of basic personal protective equipment, including surgical masks (91%) and gloves (85%) [ 24 ]. A survey of pediatric surgeons from Nigeria demonstrated similar findings, with over 90% of centers having postponed elective operations early in the pandemic [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 ] According to a survey about how Africa’s neurosurgical community has been affected by COVID-19, only 52 (16.5%) of the respondents stated they had a specific COVID-19 neurosurgery policy and only 49% felt that their response plans were satisfactory for their neurosurgical services. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%